2013
DOI: 10.1111/jcal.12010
|View full text |Cite
|
Sign up to set email alerts
|

Does social capital matter? A quantitative approach to examining technology infusion in schools

Abstract: Changing teachers' perceptions about the value of technology and equipping them with appropriate knowledge and skills in pedagogical use of technology is often regarded as a key determinant of success in technology infusion in schools. However, recent studies have indicated that changing teachers' epistemological beliefs about the use of technology in teaching and learning may not necessarily bring about change in their practice, and that technology implementation in schools can be affected by other instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
0
15
0
2
Order By: Relevance
“…In a study of 1076 teachers in 130 Hong Kong schools, Li and Choi (2014) found that the positive effect of professional development on teachers' pedagogical use of ICT was substantially less than the effect of social capital measured in two components. The first factor was the school climate and trust within the school, and the second factor was the existence of networks for accessing new information.…”
Section: 2mentioning
confidence: 99%
“…In a study of 1076 teachers in 130 Hong Kong schools, Li and Choi (2014) found that the positive effect of professional development on teachers' pedagogical use of ICT was substantially less than the effect of social capital measured in two components. The first factor was the school climate and trust within the school, and the second factor was the existence of networks for accessing new information.…”
Section: 2mentioning
confidence: 99%
“…The participants in this study, similarly, found a community of practice (albeit an online one). In turn, they will likely be future "showcasing" educators by encouraging novelty in their school community with their own expertise and on-site social capital (Li & Choi, 2013), moving from a "horizontal" mode of transferring knowledge to a given context, to a "vertical" mode, developing collective, on-site knowledge (Webb, 2011). In this manner, technological "experts" emerge in the school and help others.…”
Section: Discussionmentioning
confidence: 99%
“…Champions in technology and in integration of technology with pedagogy emerge and lead. This is a particularly important element, as Li and Choi (2013) found that: Social capital within a school seems to play a predominant role in facilitating change in pedagogical use of technology, as well as enhancing teachers' receptivity towards the use of technology in teaching and learning, and their engagement in professional development. (p. 13) Third-generation activity theory also suggests that school-based technology is developed through interactions with at least two interconnected systems-higher-level planning at a systems level (e.g., school district) and the immediate classroom context-whose processes can either impede or support success (Anthony, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Li and Choi (2013) suggested that “social capital provides the impetus for teachers to adopt a new pedagogy and that conventional models of technology infusion may not be adequate to address the social and affective dimensions of change management” (p. 14). Leaders must promote structures to create vibrant and thriving learning communities that are reflective of their contexts and learning communities.…”
Section: Key Elements In Building Professional Capitalmentioning
confidence: 99%
“…Fullan (2007, p. 50) encourages leaders to create a community of open exchange where teachers are given the opportunity to explore their own practice in handling situations ethically. Li and Choi (2013) indicate “social trust creates a context of predictability and stability for genuine, open dialogues, as well as for critical reflection and risk taking when individuals are confronted with the need for change” (p. 3). As pointed out by Hargreaves and Shirley (2009), “the point of networks is to spread innovation, stimulate learning, increase professional motivation and reduce inequities” (p. 100).…”
Section: Key Elements In Building Professional Capitalmentioning
confidence: 99%